The Progressive Supranuclear Palsy Clinical Deficits Scale. Issue 4 (17th January 2020) - Piot, Ines; Schweyer, Kerstin; Respondek, Gesine; Stamelou, Maria; ,; ,; ,; Sckopke, Philipp; Schenk, Thomas; Goetz, Christopher G.; Stebbins, Glenn T.; Höglinger, Günter U.
Abstract: Background: There is currently no undisputed, validated, clinically meaningful measure for deficits in the broad spectrum of PSP phenotypes. Objective: To develop a scale to monitor clinical deficits in patients with PSP across its broad phenotypes. Methods: The Progressive Supranuclear Palsy Clinical Deficits Scale was conceptualized to cover seven clinical domains (A kinesia‐rigidity, B radyphrenia, C ommunication, D ysphagia, E ye movements, F inger dexterity, and G ait & balance), each scored from 0 to 3 (no, mild, moderate, or severe deficits). User guidelines were developed to standardize its application. Progressive Supranuclear Palsy Clinical Deficits Scale scores were collected in patients fulfilling the MDS‐PSP diagnostic criteria in two independent, multicenter, observational studies, both cross‐sectionally (exploratory DescribePSP cohort; confirmatory ProPSP cohort) and longitudinally (12‐months' follow‐up, both cohorts). Results: Cognitive pretesting demonstrated easy scale utility. In total, 164 patients were scored (70.4 ± 7.6 years; 62% males, 35% variant phenotypes). Mean Progressive Supranuclear Palsy Clinical Deficits Scale completion time was 4 minutes. The Progressive Supranuclear Palsy Clinical Deficits Scale total score correlated with existing scales (e.g., Progressive Supranuclear Palsy Rating Scale: R = 0.88; P < 0.001). Individual Progressive Supranuclear Palsy Clinical Deficits Scale items correlated well with similar constructs in existing scales. Internal consistency (Cronbach's alpha: 0.75), inter‐rater reliability (0.96), and test‐retest stability (0.99) were acceptable. The PSP‐CDS showed significant 12‐month change (baseline, 8.6 ± 3.6; follow‐up: 10.8 ± 3.6; annualized difference: 3.4 ± 3.4; n = 49; P < 0.0001). Sample sizes required per arm for a two‐arm, 1‐year follow‐up therapeutic trial to detect 50% change in Progressive Supranuclear Palsy Clinical Deficits Scale progression was estimated to be 65 (two‐sided, two‐sample t test). Conclusion: The Progressive Supranuclear Palsy Clinical Deficits Scale is a rapidly completed, clinimetrically sound scale for clinical care and research involving PSP. © 2020 International Parkinson and Movement Disorder Society